Perception vs Reality of Financial Situation: The Emotional Role of Locus of Control - Olamide Olajide; Van Dinh; Kimberly Watkins; Anita Johnson (Journal of Financial Therapy, 2026)
This study examines how locus of control and emotions influence the divergence in perception and reality of individuals’ financial health. The findings show that comfortable emotions mediate the positive association between internal locus of control and perception-reality divergence, while uncomfortable emotions mediate the inverse effect. For individuals with a higher external locus of control, results show a negative relationship with comfortable emotions and a positive link with uncomfortable emotions. Although no direct relationship was found between external locus of control and the tendency to rate one’s financial situation higher than it is objectively, emotions act as mediators, causing these individuals to perceive their financial situation as worse than objective measures suggest. These findings, which have implications for financial therapists, planners, and counselors, reveal how locus of control, emotional states, and other demographic characteristics interact in shaping financial perceptions, offering insights into psychological and financial decision-making processes.
Keywords: divergence in financial well-being measures; emotions; life-cycle hypothesis; locus of control